ANALISIS EFISIENSI TEKNIS USAHATANI CABAI MERAH DI KECAMATAN SAWANG KABUPATEN ACEH UTARA DENGAN PENDEKATAN STOCHASTIK FRONTIER - Adhiana Adhiana; Martina Martina; Riani Riani; Suryadi Suryadi (Universitas Galuh, 2022)
Red chili is one of the leading commodities that has high economic value, it is also much needed and in demand by the community. However, the production and productivity of red chilies in Sawang District, North Aceh Regency is still low at 5.53 tons/ha, compared to the average red chili production in Aceh of 13 tons/ha. The purpose of this study was to analyze the factors that influence the production of red chili and the technical efficiency of red chili farming in Sawang District, North Aceh Regency. Sampling was carried out using the census method, which took all the existing population of 40 red chili farmers to be used as samples. The data analysis method used is the Cobb-Douglas function model with the Stochastic frontier approach. The results of the analysis show that the production factors that have a significant effect on red chili production in Sawang District are land area, labor, and fertilizer, while seed and pesticide production factors have no significant effect on red chili production. The results of the study also explained that red chili farming in the research location was technically efficient (ET=0.796).